Selection of medications in comorbidity - F. I. Belialov (Архивъ внутренней медицины, 2020)
New classification divides medications on five classes by influence on comorbid diseases and conditions and rates drug’s effects as favourable (A), possible (B), neutral (C), undesirable (D), and unfavourable (X). Class A includes drugs used in treatment of comorbid disease, class B embraced drugs with positive influence, class C includes drugs without significant influence or contradictory influence, class D consist of drugs with possible nonsevere adverse effects, and class X includes drugs with severe adverse effects. The more universal drug classification according to influence on comorbid diseases can include and unite other classifications. Classification may help unify marks of positive and negative influences drugs on comorbidity and help practitioners in selection of effective and safe treatment.